A Method for Sectioning and Immunohistochemical Analysis of Stem Cell–Derived 3‐D Organoids. (12th May 2016) - Wiley, Luke A.; Beebe, David C.; Mullins, Robert F.; Stone, Edwin M.; Tucker, Budd A.
Abstract: This unit describes a protocol for embedding, sectioning, and immunocytochemical analysis of pluripotent stem cell–derived 3‐D organoids. Specifically, we describe a method to embed iPSC‐derived retinal cups in low‐melt agarose, acquire thick sections using a vibratome tissue slicer, and perform immunohistochemical analysis. This method includes an approach for antibody labeling that minimizes the amount of antibody needed for individual experiments and that utilizes large‐volume washing to increase the signal‐to‐noise ratio, allowing for clean, high‐resolution imaging of developing cell types. The universal methods described can be employed regardless of the type of pluripotent stem cell used and 3‐D organoid generated. © 2016 by John Wiley & Sons, Inc.